GAMBARAN PENGGUNAAN TERAPI GEA (GASTROENTERITIS ) PADA PASIEN ANAK DI RSUD BATARA SIANG PANGKEP SULSEL - Wahyuni, Dwi Fitrah; Riska, Riska (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2021)
GEA (Gastroenteritis) or diarrhea is a disease caused by digestive tract disorders that are infected by bacteria. Treatment of early diarrhea, especially the choice of initial therapy, greatly affects the success of providing appropriate and appropriate therapy. This study aims to determine the rationality of therapy in pediatric patients at Batara Siang Pangkep Regional Hospital, South Sulawesi City. This study is a non-experimental study with a retrospective descriptive evaluation study using patient medical records. The samples that met the inclusion criteria were 65 patients. Acute diarrhea was mostly found in men as many as 38 patients (58%) while for women as many as 27 patients (42%). Characteristics of age 1-3 years (82%). The result showed that there are 3 therapeutic regimen in pediatric patient namely cotrimoxazole,electrolit, and zinc. So from these data meet the standards of management of diarrheal disease in children.